2020
DOI: 10.1111/ijcp.13791
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of hirsutism and hormonal parameters in acne vulgaris patients treated with isotretinoin

Abstract: Background Although the effect of isotretinoin use on hormonal changes in acne pathogenesis is not fully known, there are limited studies on its effects on the development of hirsutism. In this study, it was aimed to evaluate the effect of isotretinoin use on hirsutism and hormonal parameters in patients with acne vulgaris. Methods In this study, 30 female acne patients and 30 healthy females were evaluated prospectively. Menstrual irregularity, LH, FSH, prolactin, progesterone, 17‐OH progesterone, oestradiol,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(27 citation statements)
references
References 28 publications
(29 reference statements)
3
24
0
Order By: Relevance
“…It has been claimed that retinoids play a critical role in endometrial development and secretory differentiation, and it was found that women with menorrhagia have lower serum vitamin A levels than healthy individuals [ 28 ]. This is supported by the findings of two other studies, which reported that 33.3% and 28.3% of the females had experienced menstrual irregularities undergoing isotretinoin treatment, respectively [ 19 , 37 ]. Furthermore, a study carried out by Saljoughi, N et al reported that oligomenorrhea, amenorrhea, and dysmenorrhea were seen among 6%, 4%, and 10% of the females who were on an isotretinoin regime, respectively [ 21 ].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…It has been claimed that retinoids play a critical role in endometrial development and secretory differentiation, and it was found that women with menorrhagia have lower serum vitamin A levels than healthy individuals [ 28 ]. This is supported by the findings of two other studies, which reported that 33.3% and 28.3% of the females had experienced menstrual irregularities undergoing isotretinoin treatment, respectively [ 19 , 37 ]. Furthermore, a study carried out by Saljoughi, N et al reported that oligomenorrhea, amenorrhea, and dysmenorrhea were seen among 6%, 4%, and 10% of the females who were on an isotretinoin regime, respectively [ 21 ].…”
Section: Discussionsupporting
confidence: 82%
“…Isotretinoin is used to treat severe nodulocystic acne, and many women of reproductive age are exposed to this drug. Studies in different countries around the world have shown that isotretinoin treatment could affect the menstrual cycle [ 1 , 19 ]. Menstrual irregularities during isotretinoin therapy, including amenorrhea, can cause a great deal of concern regarding the possibility of pregnancy or permanent menstrual cycle irregularity.…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Aktar et al, FG score at the third month of treatment was found to be significantly higher than that before treatment. Clinically detected hypertrichosis was observed in 11 patients [ 18 ]. In our study, eight patients at the third month of treatment and 16 patients at the sixth month of treatment were found to have an mFG score of >8 compared to the beginning of treatment, and they were accepted as having hirsutism.…”
Section: Discussionmentioning
confidence: 99%
“…Retinoids have been shown to inhibit endometrial fibroblast and epithelial cell proliferation [ 20 ]. In a study by Aktar et al, menstrual irregularity was detected in 33.3% of the cases at the third month of treatment [ 18 ]. In the study by Karadağ et al, menstrual irregularity was observed in 28.8% of the cases during oral isotretinoin treatment [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…12 Aktar et al noted that the risk of hirsutism secondary to ISO is mostly related to peripheral increased sensitivity of androgen receptors to ISO with no associated change in the level of androgen hormones. 13 That may explain why ISO-induced hirsutism reports were not associated with additional signs of hyperandrogenism. 12 In addition to Aktar et al's results, Akpolat reported that ISO could decrease sex hormone-binding globulin (SHBG) level and increase levels of circulating free testosterone, total testosterone, and dehydroepiandrosterone sulfate (DHEAS) leading to an increase in Ferriman-Gallwey (FG) hirsutism score.…”
Section: E T T E R S T O T H E E D I T O R Isotretinoin-induced Hair ...mentioning
confidence: 99%